Metabolit Cendawan Endofit Tanaman Padi sebagai Alternatif Pengendalian Cendawan Patogen Terbawa Benih Padi - Arifda Ayu Swastini Waruwu; Bonny Poernomo Wahyu Soekarno; Abdul Munif (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Infection of seed-borne fungi on rice (Oryza sativa) may affect rice production and becomes an important problem in Indonesia recently. This study aimed to evaluate the potential of fungal endophyte metabolites isolated from rice (Oryza sativa L.) to control seed-borne pathogenic fungi. Research activities involved isolation of endophytic fungi from rice, isolation of seed-borne fungi, and inhibition test of isolated endophytic fungal metabolites on seed-borne pathogenic fungi. The results showed that 3 isolates of endophytic fungi, i.e. LA6, LA11, and LA14 were potential producing antifungal metabolite. The metabolites of LA11 and LA14 isolates was able to reduce the growth of seed-borne pathogenic fungi between 18.33 and 47.28%.